Debris and smear layer removal efficacy and changes in morphology of dentinal tubules after using citric acid, tetracycline-hydrochloride and mixture of tetracycline and acid and detergent - Ahmad Moghare Abed; Shirin Zahra Farhad; Alireza Farhad; Mehrdad Barekatain; Morvarid Mafi; Mohammad Shah Abooie (Wolters Kluwer Medknow Publications, 2013)
Background: In periodontal diseases, contamination of roots with bacteria and their active biologic agents and smear layer formation following periodontal treatments, prevents reattachment of periodontal cells. As a matter of fact biomodification of root surface and removal of smear layer and debris is critical for regeneration of periodontal structures. The aim of this study was to compare the efficacy of smear layer removal by citric acid, tetracycline-hydrochloride (TTC-HCL) and mixture of tetracycline and acid and detergent (MTAD). Materials and Methods: In this in vitro and experimental study, 12 impacted third molars were sectioned from cervical enamel junction (CEJ) to mid-root area into four dentinal specimens ( n = 48). Three groups were conditioned by citric acid 3%, TTC-HCL 50 mg/mL and MTAD by means of cotton pellets, which were changed every 30 s for 3 min. The control group was conditioned by distilled water. Images from scanning electron microscope (SEM) were examined by two different analyzers. Data was analyzed by Kroskal Wallis and Mann - Whitney statistical analysis. Results: The mean of dentinal tubules diameter was the most in MTAD group and the least in TTC-HCL and this difference was statistically significant ( P = 0.05). Conclusion: According to the present study, TTC-HCL could remove debris and smear layer but citric acid and MTAD had better debris and smear layer removal efficacy and demineralization effect in comparison with TTC-HCL.